The Dialectics Of Supervision And The Entrepreneurial Competence Of Madrasah Principals: A Critical Study Of Madrasah Ibtidaiyah In Gresik Regency - Ririn Inayatul Mahfudloh; Nurul Hidayati; Marjuki; Khusnan Iskandar; Muhammad Hasyim; Rian Nur Farezi; Fionaldo Satria Devangga (Indonesian Journal of Educational Science (IJES), 2026)
This study aims to analyze the role of educational supervision in enhancing the entrepreneurial competence of Madrasah Ibtidaiyah principals in Gresik Regency. The research employed a qualitative approach with a descriptive design, utilizing in-depth interviews, observations, and documentation studies involving madrasah supervisors and principals as the primary informants.The findings reveal that educational supervision has transformed from a merely administrative function into a collaborative approach oriented toward strengthening entrepreneurial leadership capacity. Madrasah supervisors play strategic roles as facilitators, mentors, and partners through the implementation of mentoring, coaching, structured training, and continuous assistance. Contextual and needs-based supervision strategies have proven effective in improving the entrepreneurial competence of madrasah principals, particularly in terms of program innovation, resource management, and partnership network development.The enhancement of entrepreneurial competence has significantly contributed to the transformation of madrasah management, as reflected in improved managerial effectiveness, learning innovation, and institutional financial independence. These findings indicate that supervision functions as an enabling system in fostering adaptive and sustainable entrepreneurial leadership.This study recommends strengthening supervision models grounded in mentoring and collaboration as a systemic strategy for the development of Islamic education management. The implications of this research extend beyond improving educational quality, contributing also to economic capacity building and community empowerment through madrasah-based entrepreneurship programs